Exercise in the Park or Gym? The Physiological and Mental Responses of Obese People Walking in Different Settings at Different Speeds: A Parallel Group Randomized Trial - Wang, Xinxin; Zhou, Quanfu; Zhang, Mingjuan; Zhang, Qinghai (Frontiers in Psychology, 2021)
Evidence shows physical activity has multiple health benefits for one’s body and mind, but little is known about the impacts of setting and intensity on exercise experience, especially for obese people. This study investigated the physiological and psychological effects of four walking conditions with different setting (park vs. gym) and intensity (slow vs. fast) on young obese adults. Subjects were Chinese university students (N=77) aged 18–21, who were diagnosed as obese. They were randomly assigned to participate in one of the four activities in the field: slow walk in the park (2.8km/h), fast walk in the park (5.5km/h), slow walk in the gym, and fast walk in the gym. Physiological indexes, including blood pressure and heart rate, were measured before and after the walking. Psychological responses were measured by the Symbol Digit Modalities Test, the mood states scale, and the semantic differential scale. This study of obese people aged 18-21 confirmed previous findings that exercising in natural environments better relieved stress and restored attentional levels than indoor activities. The results suggested that participants’ mood states and their environmental perceptions may be influenced by the walking conditions with different setting and speed. The findings can be used in the planning and design urban green spaces for promoting physical activity, and making exercise plans for obese people.